Prevenção à doença renal crônica na estratégia de saúde da família - AGUIAR, Valdenici Firmo de (2019)
Chronic Kidney Disease is understood as a clinical syndrome that has negative impacts on public health worldwide. The objective of the study was to analyze the actions for prevention of Chronic Kidney Disease performed by professionals of the Family Health Strategy. This is a descriptive research with a qualitative approach. Data collection took place from June to August 2019, through semi-structured interviews, following a previously tested script, whose speeches were recorded and transcribed in full. The sample consisted of 15 professionals. From the interviews, two categories emerged: Conceptions of Chronic Kidney Disease prevention and Team Doing. The speeches revealed the conception that the prevention of the disease is related to the transfer of orientations about healthy habits and the clinical medical monitoring. As for the practices, there was lack of coordination of care and fragmented work process, realizing the need to define flows, promote intersectoral integration and interprofessionality. At the same time, the professionals emphasized the home visit and its importance to know the life reality of the families. However, they demonstrated that the educational actions practiced during the home visit are performed vertically. These results point to health education and control of underlying diseases, but the prescriptive biomedical view stands out, to the detriment of valuing dialogue and empowering subjects. It is believed that these results may promote reflections on Chronic Kidney Disease prevention and support interventions for professional qualification, fixation of professionals in teams and organization of work processes, improving preventive actions and reflecting on improvements in the quality of care provided to users and their families.